2022
DOI: 10.3390/ijerph192316010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long COVID-19 Caused by Different SARS-CoV-2 Strains: A Systematic Review and Meta-Analysis

Abstract: Although many studies of long COVID-19 were reported, there was a lack of systematic research which assessed the differences of long COVID-19 in regard to what unique SARS-CoV-2 strains caused it. As such, this systematic review and meta-analysis aims to evaluate the characteristics of long COVID-19 that is caused by different SARS-CoV-2 strains. We systematically searched the PubMed, EMBASE, and ScienceDirect databases in order to find cohort studies of long COVID-19 as defined by the WHO (Geneva, Switzerland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 75 publications
5
47
0
2
Order By: Relevance
“…Similar results have been found in the meta-analysis by Du et al (Du et al, 2022). These authors pooled data for post-COVID pain and, surprisingly, observed that the prevalence of this symptom was higher in patients infected with the Omicron variant (11.7%) as compared with those infected with the historical strain (9.4%) (Du et al, 2022). The only study specifically comparing the prevalence of musculoskeletal post-COVID pain between different SARS-COV-2 variants found that post-COVID pain was more prevalent in individuals infected with the historical/wild-type strain (47.7%) than in those infected with the Alpha (38.3%) or Delta (41%) variants (Fernández-de-las-Peñas, Cancella-Cilleruelo, et al, 2022).…”
Section: Covid Painsupporting
confidence: 91%
“…Similar results have been found in the meta-analysis by Du et al (Du et al, 2022). These authors pooled data for post-COVID pain and, surprisingly, observed that the prevalence of this symptom was higher in patients infected with the Omicron variant (11.7%) as compared with those infected with the historical strain (9.4%) (Du et al, 2022). The only study specifically comparing the prevalence of musculoskeletal post-COVID pain between different SARS-COV-2 variants found that post-COVID pain was more prevalent in individuals infected with the historical/wild-type strain (47.7%) than in those infected with the Alpha (38.3%) or Delta (41%) variants (Fernández-de-las-Peñas, Cancella-Cilleruelo, et al, 2022).…”
Section: Covid Painsupporting
confidence: 91%
“…We used data from several sources, including the Global Health Expenditure Database and Global Health Observatory data from the World Health Organization (WHO) [ 40 ], as well as World Bank Open Data [ 20 ]. Data regarding COVID-19 related outcomes, i.e., cases, deaths, and percent of the vaccinated population, were obtained from WHO’s publicly available COVID-19 dashboard [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since the beginning of the pandemic, there has been considerable effort to contain the virus, including restrictive measures from governments [ 19 ] as well as efforts from researchers to understand the pandemic’s evolution and control. Some key areas of inquiry have been potential symptoms [ 20 ] and therapies [ 21 ], the effect of the pandemic on lifestyle factors such as diet [ 22 ], understanding the mechanism of transmission and human–pathogen interactions [ 23 , 24 , 25 ], and perhaps most crucially, vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS‐CoV‐2 subvariants were not detected for patients in our study, the majority of COVID‐19 cases in the fifth wave of the Hong Kong outbreak were caused by Omicron BA.2 and related sublineages, the largest monophyletic lineage was BA.2.2, and only with limited detection of Omicron BA.1 and related sublineages and Delta AY.127 12 . A systematic review indicated that the prevalence of Omicron‐induced long COVID in 3 months (28.4%) was lower than other strains (wild‐type: 52.1%, Alpha: 65.8%, Delta: 34.6%) 27 . The milder symptoms of Omicron may represent less damage in organs than the previous variants, resulting in a lower prevalence of long COVID 14 .…”
Section: Discussionmentioning
confidence: 99%
“…12 A systematic review indicated that the prevalence of Omicron-induced long COVID in 3 months (28.4%) was lower than other strains (wild-type: 52.1%, Alpha: 65.8%, Delta: 34.6%). 27 The milder symptoms of Omicron may represent less damage in organs than the previous variants, resulting in a lower prevalence of long COVID. 14 Compared with other studies with different follow-up period of long COVID in Omicron cases, the prevalence of long COVID during 6-12 months postacute infection in Hong Kong is higher, for example, 8.2% of COVID-19 survivors reported long COVID symptoms at 73 days after the infection in Eastern India, 10.9% at 2 months in United States, 4.5% at 4 weeks in United Kingdom, and 18.5% at 6 months in South Africa.…”
Section: Discussionmentioning
confidence: 99%